Four blind alleys of scenario analysis. Issue 6 (11th November 2014) - Harris, Gerald
Abstract : Purpose: – Some scenario projects, especially those that take short cuts, have design flaws that undermine the whole purpose of scenario analysis. This article aims to investigate these. Design/methodology/approach: – This article is a guide to avoiding four common project flaws. Findings: – Selecting one desired future and using scenario analysis to promote it to the exclusion of other possibilities is not a wise approach. Practical implications: – Scenarios that ignore the likelihood of serious competition from fledgling startups, market invaders from other industries, or even the possibility of several companies combining to gain the competencies needed to be a threat, are not addressing the future's full spectrum of competitive uncertainty. Originality/value: – By becoming aware of the four "blind alleys" of scenario analysis warned about in this article, practitioners are more likely to use this planning tool effectively to scope out the true outlines of uncertainty or the fallout from discontinuity and prepare their firm to cope with new realities.